2012
DOI: 10.1007/s00216-012-5845-6
|View full text |Cite
|
Sign up to set email alerts
|

Advances and trends in the design, analysis, and characterization of polymer–protein conjugates for “PEGylaided” bioprocesses

Abstract: In addition to their use as therapeutics and because of their enhanced properties, PEGylated proteins have potential application in fields such as bioprocessing. However, the use of PEGylated conjugates to improve the performance of bioprocess has not been widely explored. This limited additional industrial use of PEG-protein conjugates can be attributed to the fact that PEGylation reactions, separation of the products, and final characterization of the structure and activity of the resulting species are not t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…Various parameters were mentioned for lower biological activity of PEGylated protein, including PEG molecular weight, number of attached PEG chains and PEGylation site [36]. Moreover, masking of the amino acid sites that are critical for binding to other molecules by PEG chains may alter the affinity of hGH for its receptor [37].…”
Section: Systemmentioning
confidence: 99%
“…Various parameters were mentioned for lower biological activity of PEGylated protein, including PEG molecular weight, number of attached PEG chains and PEGylation site [36]. Moreover, masking of the amino acid sites that are critical for binding to other molecules by PEG chains may alter the affinity of hGH for its receptor [37].…”
Section: Systemmentioning
confidence: 99%
“…It has been shown that the reactive amino acids that often participate during this conjugation process are arginine, aspartic acid, histidine, lysine, cysteine, glutamic acid, threonine, tyrosine, and serine. Other than that, N-terminal amino group and the C-terminal carboxylic acid are also found to be involved with these reactions [105]. …”
Section: Pegylation Carriers Of Therapeutic Proteins and Genesmentioning
confidence: 99%
“…As with almost any protein therapeutic, there are issues with the manufacture, characterization, and use of PEGylated proteins [70][71][72][73][74][75], including the potential induction of anti-PEG antibodies [76], especially in the case of hyperPEGylated products that contain large numbers of conjugated PEG molecules [77][78]. Many proteins used as therapeutics display some propensity for immunogenicity [79][80][81][82][83][84].…”
Section: Protein Pegylationmentioning
confidence: 99%